A Specific IL6 Polymorphic Genotype Modulates the Risk of Trypanosoma cruzi Parasitemia While IL18, IL17A, and IL1B Variant Profiles and HIV Infection Protect Against Cardiomyopathy in Chagas Disease - Gomes dos Santos, Alexandra; Watanabe, Elieser Hitoshi; Ferreira, Daiane Tomomi; Oliveira, Jamille; Nakanishi, Érika Shimoda; Oliveira, Claudia Silva; Bocchi, Edimar; Novaes, Cristina Terra Gallafrio; Cruz, Fatima; Carvalho, Noemia Barbosa; Sato, Paula Keiko; Yamashiro-Kanashiro, Edite Hatsumi; et al. (Frontiers in Immunology, 2020)
Background. Chagas disease caused by Trypanosoma cruzi (T. cruzi) affects approximately six million individuals worldwide. Clinical manifestations are expected to occur due to the parasite persistence and host immune response. Herein we investigated potential associations between IL1B, IL6, IL17A or IL18 polymorphism profiles and cardiomyopathy or T. cruzi parasitemia, as well as the impact of HIV infection on cardiopathy. Methods. 206 patients and 90 control individuals were analyzed. IL1B rs1143627 T>C, IL6 rs1800795 C>G, IL17A rs2275913 G>A, IL18 rs187238 C>G, and IL18 rs1946518 C>A SNVs were analyzed by real-time PCR and T. cruzi parasitemia by PCR. Results. Our data revealed association between a cytokine gene polymorphism and parasitemia never previously reported. The IL6 rs1800795 CG genotype lowered the risk of positive parasitemia (OR=0.45, 95% CI 0.24–0.86, P=0.015). Original findings included associations between IL17A rs2275913 AA and IL18 s1946518 AA genotypes with decreased risk of developing cardiomyopathy (OR=0.27, 95% CI 0.07-0.97, P=0.044; and OR=0.35, 95% CI 0.14-0.87, P=0.023, respectively). IL18 rs1946518 AA and IL1B rs1143627 TC were associated with reduced risk for cardiomyopathy severity, including NYHA (New York Heart Association) class≥ 2 (OR=0.21, 95% CI 0.06-0.68, P=0.009; and OR=0.48, 95% CI 0.24-0.95, P=0.036, respectively) and LVEF (Left Ventricular Ejection Fraction) <45% for IL18 rs1946518 AA (OR=0.22, 95% CI 0.05-0.89, P=0.034). A novel, unexpected protective effect of HIV infection against development/progression of cardiomyopathy was identified, based on a lower risk of developing cardiopathy (OR=0.48, 95% CI 0.23-0.96, P=0.039), NYHA class≥2 (OR=0.15, 95% CI 0.06-0.39, P<0.001) and LVEF<45% (OR=0.03, 95% CI 0.00-0.25, P=0.001). Digestive involvement was negatively associated with NYHA ≥2 and LVEF<45% (OR=0.20, 95% CI 0.09-0.47, P<0.001; and OR=0.24, 95% CI 0.09-0.62, P=0.004, respectively). Conclusions. Our data support a protective role of IL17A AA, IL18 AA and IL1B TC genotypes against development/progression of cardiomyopathy and a modulatory effect of the IL6 CG genotype on the risk of parasitemia in Chagas disease. Notably, HIV infection was shown to protect against development/progression of cardiopathy, potentially associated with a synergistic effect of HIV and HAART, attenuating a Th1-mediated response in the myocardium. This proposed hypothesis requires confirmation, however, in larger and more comprehensive future studies.